THE IMPLEMENTATION OF ENGLISH MEDIUM INSTRUCTION IN TEACHING ENGLISH FOR SIXTH GRADER OF A PRIVATE ELEMENTARY SCHOOL (RETAIN, 2017)
THE IMPLEMENTATION OF ENGLISH MEDIUM INSTRUCTION IN TEACHING ENGLISH FOR SIXTH GRADER OF A PRIVATE ELEMENTARY SCHOOL Pandu Prasetyo Agung Pambudi English Education, Faculty of Languages and Arts, State University of Surabaya 12020084041.pandup@mhs.unesa.ac.id Ahmad Munir English Education, Faculty of Languages and Arts, State University of Surabaya ahmadmunir@unesa.ac.id Abstrak Kemampuan berkomunikasi menggunakan bahasa asing sangat penting dan hal tersebut pertama kali terlihat dari kemampuan bertutur kata. Maka dari itu, Bahasa Inggris sebagai bahasa pengantar (EMI) sangat cocok untuk mengajar siswa Bahasa Inggris sebagai bahasa asing. EMI adalah situasi kelas dimana Bahasa Inggris digunakan sebagai bahasa pengantar antara pengajar dan siswa dalam berkomunikasi. Peneliti mempertanyakan sebuah klaim dari salah satu sekolah dasar swasta di Surabaya, dimana mereka mengklaim menerapkan EMI sepenuhnya dalam mengajar Bahasa Inggris untuk siswa kelas enam Sementara itu, penerapan EMI sangat kontroversial dan tidak sepenuhnya dalam Bahasa Inggris. Penelitian ini bertujuan untuk mendeskripsikan bagaimana guru menerapkan EMI dalam mengajar Bahasa Inggris untuk siswa kelas enam (2) respons dan opini siswa terhadap penerapan EMI dalam pembelajaran Bahasa Inggris. Penelitian ini menggunakan desain penelitian kualitatif. Penelitian ini melibatkan 13 orang siswa kelas enam sebagai subjek penelitian yang di amati sebanyak tiga kali selama pelajaran Phonics Bahasa Inggris dan perwakilan kelas diwawancarai setelahnya. Hasil penelitian yang telah didapatkan menunjukkan bahwa guru menerapkan EMI hampir diseluruh langkah pembelajaran yang menyerupai langkah Straight Arrows ESA. EMI dapat diterapkan karena kegiatan pembelajarannya menguntungkan pelajar bahasa muda. Instruksi yang diberikan dalam Bahasa Inggris hampir seluruhnya direspon dengan baik sebagaimana guru menerapkannya melalui permainan, penjelasan yang selalu bermula dari pengetahuan awal siswa dan pembacaan teks menyeluruh. Terlebih lagi, hasil dari wawancara menunjukkan bahwa para siswa berpikiran positif tentang penerapan EMI. Maka dari itu, penerapan EMI pada siswa kelas enam dapat dilakukan dan di rekomendasikan. Kata kunci: Bahasa Inggris sebagai bahasa pengantar, Pelajar Muda, Respon, Pendapat. Abstract The capability in communicating in the Foreign Language is important as it is initially seen from the oral performance. Thus, English Medium Instruction (EMI) is suitable for teaching EFL learner. It is a classroom setting where the English language is used as means of communication between instructor and learners. The researcher questions a claim of a private elementary school in Surabaya, in that they implement EMI in teaching English for sixth graders in full. Meanwhile, EMI was controversial and their implementations were mostly not in full English. This research was aimed at describing how the teacher implements English Medium Instruction in teaching English lesson for sixth graders. (2.) the students’ responses and opinions toward the implementation of English Medium Instruction in learning English lesson. The data is analyzed qualitatively. A qualitative research design was used in this study. This study involved one English teacher and 13 sixth grader students as the participants of the study which observed three times during English phonics lesson and the representation of the whole class interviewed after. The result which was gotten shows that the teacher implemented EMI in almost all of the teaching stages which similar to Straight Arrows ESA sequence. It is applicable as the teaching activities favor young language learner. The instructions which delivered in English are mostly responded well as the teacher implemented it through games, explanation which relate to students’ prior knowledge and whole passage reading. Moreover, the result of interview revealed that the students have positive thoughts about the teaching-learning process. Therefore, the implementation of English Medium Instruction in teaching English lesson for sixth grader is applicable and recommended. Keywords: English Medium Instruction, Young Learner, Response, Opinion.